Quality changes in fresh-cut celery as affected by heat treatment and storage - Viña, Sonia Zulma (2007)
This work was intended to investigate the effect of thermal treatment (by immersion or heated air) on quality attributes of pre‐cut celery stored at 0 °C for 21 days. The evolution of organoleptic characteristics, weight loss, surface color, chlorophyll content, texture and microbiological counts were determined. Quality of cut celery mostly maintained its initial level up to 14 days at 0 °C, regardless of the treatment applied. The control and heated‐air‐treated samples experienced a similar evolution of surface color, chlorophyll content, texture and microbial counts. There was a slight advantage of the heated air treatment compared to the control, as measured by sensory parameters. The immersion treatment allowed a better retention of the original color and the total chlorophyll content of pieces. However, after 14 days at 0 °C, a more noticeable tissue softening along with rapid microbial development was observed. Copyright © 2007 Society of Chemical Industry